(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In the globalization era, freedom of expression takes place, encouraging interior styles to experience mobal/mubal conditions, needing pillars of development direction. Memayu Hayuning Bawono was an interesting philosophical concept and life goal of Javanese people discussed in connection with the development of interior design in the Nusantara in the global era. Discussion with a critical approach to answering two formulations of the problem: why the concept of memayu hayuning bawono is needed in the development of the Nusantara interior and how the implementation of the concept of memayu hayuning bawono as a pillar of the development of the interior design of the Nusantara so far was happening. The results of the discussion showed me Mayu Hayuning Bawono as a philosophy of life giving birth to the interior style of a traditional house having the value of edi, peni, apik, and endah to maintain the beauty of natural life proved to still be a pillar of the Nusantara interior development among the hustle and bustle of the emergence of various interior styles. The facts showed that the tradition of the interior style of the house has become a magical power for the tradition of living with an interior to the present era. Visualized cultural symbols form the elements of the interior and are presented as a romantic style of past life. Traditional values were oriented into commodity objects and were positioned as interiors of socialite places.